Risk Mitigation Strategy; Parental Involvement To Enhance Early Childhood Learning - Efrita Norman; Hasan Baharun; Ririn Iswandari; Sunarsih Sunarsih; Lutfiatul Iltiqoiyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to analyse and understand the risk mitigation of Coronavirus Disease (COVID-19) through parental involvement in early childhood learning activities. It employs a qualitative approach within a case study research design. The research locations cover (1) Al-Iman Islamic Kindergarten, (2) Irtiqoiyah Islamic Kindergarten, and (3) Masyitoh Islamic Kindergarten, Probolinggo, East Java, Indonesia. The results show that these kindergartens apply the same method in learning activities during the Covid-19 pandemic. They use familiar and straightforward electronic media that actively involve parents in student learning enhancement. Apart from this, the parental-involvement strategy incorporates two-way communication between teachers and parents of students, which opens opportunities to solve student learning problems. The findings of this study are collaborative parenting in making learning activities effective in schools. This research has implications for the importance of the cooperation of parents and teachers in making learning effective to achieve the specified goals.